Low-shrinkage ceramic green body particle size grading design method and application thereof in quartz ceramic preparation

By optimizing the particle size grading of quartz particles in the quartz ceramic core, the mass distribution ratio of particles is improved, and the problem of insufficient mechanical properties of quartz ceramic core at high temperatures is solved, and its mechanical properties and dimensional stability are significantly improved.

CN119416284AActive Publication Date: 2025-02-11CENT SOUTH UNIV +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411445970.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-11
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The existing quartz ceramic cores have insufficient mechanical properties at high temperatures and have poor dimensional stability, which affects the production pass rate of hollow blades.

Method used

By optimizing the particle size grading of quartz particles, selecting four particle sizes for grading, determining the θ value of the tangent of spherical particles of adjacent particle sizes, and querying the spherical code table to determine the size of small particles around large particle size particles that can be employed by small particles. The quantity of particles is wrapped, and the mass distribution ratio of particles is derived based on the mass calculation formula to obtain the best grading plan.

Benefits of technology

The mechanical properties and dimensional stability of the quartz ceramic core are significantly improved, especially the bending strength under high temperature conditions, and the problem of insufficient high temperature strength of the quartz ceramic core is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119416284A_ABST
    Figure CN119416284A_ABST
Patent Text Reader

Abstract

The invention discloses a grain size grading design method of a low-shrinkage ceramic green body and application of the grain size grading design method in quartz ceramic preparation, and belongs to the technical field of ceramic materials. By optimizing the particle size grading of quartz, cristobalite crystallization in the preparation process of the quartz ceramic is promoted, the sintering densification is improved, and the mechanical property and the size stability of the quartz ceramic, especially the bending strength under the high-temperature condition, are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a method for designing particle size gradation of a low-shrinkage ceramic body and an application thereof in the preparation of quartz ceramics. Background Art

[0002] Currently, there are two main types of ceramic cores commonly used for high-temperature alloy blade casting. One is an aluminum-based core with special alumina as the main component, and the other is a quartz ceramic core with fused quartz as the main matrix material. The main performance requirements of the core are to be able to withstand the thermal shock of the molten metal during high-temperature alloy casting, have excellent mechanical properties and dimensional stability at high temperatures, and quickly remove chemicals after casting.

[0003] Quartz ceramic core is a key material in the manufacture of hollow blades. Its mechanical properties and dimensional stability directly affect the production qualification rate of hollow blades. In the prior art, although quartz ceramic core has the advantage of fast chemical removal, its high-temperature mechanical properties are insufficient. Therefore, in the preparation process of quartz ceramic core, the particle size grading has an important influence on the performance of quartz ceramic core, but there is still a lack of systematic research and optimization methods. Summary of the invention

[0004] In order to solve the problem of insufficient high temperature performance of quartz ceramics, the present invention proposes a low shrinkage ceramic body particle size gradation design method and its application in quartz ceramic preparation. By optimizing the particle size gradation of quartz, the dimensional stability and high temperature mechanical properties of the quartz ceramic core are improved.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a method for designing particle size distribution of a low shrinkage ceramic body, comprising the following steps:

[0007] Sort the particle sizes by size, and regard different particle sizes as different diameters of equal-diameter spheres; select four particle sizes for grading, and determine the θ value at which two adjacent spherical particles are tangent to each other; query the spherical code table by the θ value to obtain how many spherical particles of small diameter can be wrapped around a spherical particle of large diameter; deduce the mass distribution ratio of spherical particles of two adjacent particle sizes according to the mass calculation formula and the sphere volume calculation formula, and obtain the optimal grading scheme;

[0008] Among them, the particle sizes of the four particles are R 1 , R 2 , R 3 and R 4 , R 2 =0.633R 1 , R 3 =0.633R1 ×0.414, R 4 =0.633R 1 ×0.225;

[0009] Without considering the intermolecular forces, the particle size selection is based on the relationship between the particle radius ratio and the coordination number. If the stacking method with the highest probability is selected to determine the number of small-sized spheres in the stacking gaps of large-sized spheres and the polyhedral structure they form, the above four particle sizes can be derived;

[0010] R 1 With R 2 The θ value of the tangent spherical particles of two particle sizes is calculated by equations (1) and (2);

[0011] sin01=R1 / (R1+R2)(1)

[0012] 0 = 2arcsin01(2)

[0013] R 2 With R 3 The θ value of the tangent of two spherical particles of different particle sizes, R 3 With R 4 The calculation method of θ value of tangency between spherical particles of two particle sizes is the same as above;

[0014] Then, the mass distribution ratio of spherical particles of two adjacent particle sizes is calculated according to formula (3):

[0015]

[0016] In formula (3), m t is the mass of the t-level particles; m z is the mass of the z-level particle; k is the number of layers of the t-level particle encapsulating the z-level particle; R t is the radius of the t-level particle; R z is the radius of the z-level particle; Xt z is the number of z-level particles encapsulated by t-level particles;

[0017] The source of the spherical code table is SLOANE NJ A. Nice arrangements of points on a sphere in various dimensions: Tables of Spherical Codes [R / OL]. (2012-1-15) [2024-03-20]. http: / / neilsloane.com / packings / dim3 / .

[0018] See the schematic diagram of a large-size spherical particle surrounded by a small-size spherical particle. Figure 1 .

[0019] Preferably, k=1 or 2.

[0020] In the present invention, R 1 , R 2 , R 3 and R 4 Satisfy R 2 =0.633R 1 , R 3 =0.633R 1 ×0.414, R 4 =0.633R 1 ×0.225, mainly because, without considering the intermolecular forces, the particle size selection is based on the relationship between the particle radius ratio and the coordination number, and the number of small-size spheres in the large-size sphere stacking gap and the polyhedral structure they form are determined by selecting the most probable stacking method. The above four particle sizes can be derived according to the above ideas.

[0021] The second technical solution of the present invention: a preparation process of quartz ceramics, comprising the following steps:

[0022] According to the above-mentioned low shrinkage ceramic body particle size gradation design method, the mass ratio of quartz particles of different particle sizes is calculated, the quartz particles are melted, a basic mineralizer is added, and then a molten plasticizer is added to obtain a mixed slurry, and the mixed slurry is injected into a mold, sintered, and cooled to obtain quartz ceramics.

[0023] Preferably, the basic mineralizer is a combination of one or more of cerium oxide, zirconium oxide and titanium oxide.

[0024] More preferably, the particle size range of the quartz particles is 100-1000 mesh; the particle size of the cerium oxide is 300-500 mesh; the particle size of the zirconium oxide is 300-500 mesh; and the particle size of the titanium oxide is 600-800 mesh.

[0025] More preferably, the base mineralizer is cerium oxide, zirconium oxide and titanium oxide.

[0026] More preferably, by mass, the quartz particles account for 70 to 100 parts, the cerium oxide accounts for 1 to 5 parts, the zirconium oxide accounts for 10 to 20 parts, the titanium oxide accounts for 10 to 20 parts and the plasticizer accounts for 15 to 20 parts.

[0027] Preferably, the plasticizer consists of paraffin, beeswax and polyethylene in a mass ratio of 88-92:5-8:1-5.

[0028] Preferably, when the mixed slurry is injected into the mold, the injection pressure is 3-6 MPa.

[0029] The beneficial technical effects of the present invention are as follows:

[0030] The present invention optimizes the particle size gradation of quartz, promotes the crystallization of cristobalite in the preparation process of the quartz ceramic core, improves the sintering densification, and significantly increases the mechanical properties and dimensional stability of the quartz ceramic core, especially the bending strength under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the spherical particles with large particle size being surrounded by spherical particles with small particle size in the present invention. DETAILED DESCRIPTION

[0032] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0033] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0034] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0035] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0036] Example 1

[0037] A low shrinkage ceramic body particle size gradation design scheme and its application in quartz ceramic preparation, the steps are as follows:

[0038] Step 1, select R 1 =100μm, select the mass ratio range of k=2, and the calculation results are: primary particles: 9.63%, secondary particles: 30.32%, tertiary particles: 40.21%, and quaternary particles: 19.84%.

[0039] The specific mass ratio used is: primary particles: 10%, secondary particles: 30%, tertiary particles: 40%, and quaternary particles: 20%.

[0040] Step 2, weigh 4 kg of fused quartz, cerium oxide, zirconium oxide, and titanium oxide as solid powders in proportion (in the solid powders, the mass percentages of fused quartz, cerium oxide, zirconium oxide, and titanium oxide are 70%, 2%, 14%, and 14%, respectively); weigh 800 g of paraffin, beeswax, and polyethylene in a mass ratio of 91:7:2 and mix them, heat and melt to obtain a mixed solution, pour the evenly mixed solid powder into the mixed solution, and stir for 20 hours to obtain a uniform ceramic slurry.

[0041] Step 3, placing the slurry in a die-casting machine, injecting the slurry into a core mold at a pressure of 4 MPa, and then sintering to obtain a quartz ceramic core.

[0042] Example 2

[0043] A low shrinkage ceramic body particle size gradation design scheme and its application in quartz ceramic preparation, the steps are as follows:

[0044] Step 1, select R 1 =60μm, select the mass ratio range of k=2, and the calculation results are: primary particles: 9.63%, secondary particles: 30.32%, tertiary particles: 40.21%, and quaternary particles: 19.84%.

[0045] The specific mass ratio used is: primary particles: 10%, secondary particles: 30%, tertiary particles: 40%, and quaternary particles: 20%.

[0046] Step 2, weigh 4 kg of fused quartz, cerium oxide, zirconium oxide, and titanium oxide as solid powders in proportion (in the solid powders, the mass percentages of fused quartz, cerium oxide, zirconium oxide, and titanium oxide are 70%, 2%, 14%, and 14%, respectively); weigh 800 g of paraffin, beeswax, and polyethylene in a mass ratio of 91:7:2 and mix them, heat and melt to obtain a mixed solution, pour the evenly mixed solid powder into the mixed solution, and stir for 20 hours to obtain a uniform ceramic slurry.

[0047] Step 3, placing the slurry in a die-casting machine, injecting the slurry into a core mold at a pressure of 4 MPa, and then sintering to obtain a quartz ceramic core.

[0048] Example 3

[0049] A low shrinkage ceramic body particle size gradation design scheme and its application in quartz ceramic preparation, the steps are as follows:

[0050] Step 1, select R 1=40μm, select the mass ratio range of k=2, and the calculation results are: primary particles: 9.63%, secondary particles: 30.32%, tertiary particles: 40.21%, and quaternary particles: 19.84%.

[0051] The specific mass ratio used is: primary particles: 10%, secondary particles: 30%, tertiary particles: 40%, and quaternary particles: 20%.

[0052] Step 2, weigh 4 kg of fused quartz, cerium oxide, zirconium oxide, and titanium oxide as solid powders in proportion (in the solid powders, the mass percentages of fused quartz, cerium oxide, zirconium oxide, and titanium oxide are 70%, 2%, 14%, and 14%, respectively); weigh 800 g of paraffin, beeswax, and polyethylene in a mass ratio of 91:7:2 and mix them, heat and melt to obtain a mixed solution, pour the evenly mixed solid powder into the mixed solution, and stir for 20 hours to obtain a uniform ceramic slurry.

[0053] Step 3, placing the slurry in a die-casting machine, injecting the slurry into a core mold at a pressure of 4 MPa, and then sintering to obtain a quartz ceramic core.

[0054] Comparative Example 1

[0055] A low shrinkage ceramic body particle size distribution design scheme and its application in quartz ceramic preparation:

[0056] The difference between this comparative example and Example 1 is that the mass ratio of the first-level to fourth-level fused quartz particles in step 1 is different, and the other raw materials and steps are the same as those in Example 1; the specific mass ratio of the first-level to fourth-level fused quartz particles is: first-level particles: 5%, second-level particles: 20%, third-level particles: 40%, and fourth-level particles: 35%.

[0057] Comparative Example 2

[0058] A low shrinkage ceramic body particle size distribution design scheme and its application in quartz ceramic preparation:

[0059] The difference between this comparative example and Example 1 is that the mass ratio of the first-level to fourth-level fused quartz particles in step 1 is different, and the other raw materials and steps are the same as those in Example 1; the specific mass ratio of the first-level to fourth-level fused quartz particles is: first-level particles: 35%, second-level particles: 35%, third-level particles: 20%, and fourth-level particles: 10%.

[0060] Comparative Example 3

[0061] A low shrinkage ceramic body particle size distribution design scheme and its application in quartz ceramic preparation:

[0062] The difference between this comparative example and Example 2 is that the mass ratio of the first-level to fourth-level fused quartz particles in step 1 is different, and the other raw materials and steps are the same as those in Example 1; the specific mass ratio of the first-level to fourth-level fused quartz particles is: first-level particles: 5%, second-level particles: 20%, third-level particles: 40%, and fourth-level particles: 35%.

[0063] Comparative Example 4

[0064] A low shrinkage ceramic body particle size distribution design scheme and its application in quartz ceramic preparation:

[0065] The difference between this comparative example and Example 2 is that the mass ratio of the first-level to fourth-level fused quartz particles in step 1 is different, and the other raw materials and steps are the same as those in Example 1; the specific mass ratio of the first-level to fourth-level fused quartz particles is: first-level particles: 35%, second-level particles: 35%, third-level particles: 20%, and fourth-level particles: 10%.

[0066] Comparative Example 5

[0067] A low shrinkage ceramic body particle size distribution design scheme and its application in quartz ceramic preparation:

[0068] The difference between this comparative example and Example 3 is that the mass ratio of the first-level to fourth-level fused quartz particles in step 1 is different, and the other raw materials and steps are the same as those in Example 1; the specific mass ratio of the first-level to fourth-level fused quartz particles is: first-level particles: 5%, second-level particles: 20%, third-level particles: 40%, and fourth-level particles: 35%.

[0069] Comparative Example 6

[0070] A low shrinkage ceramic body particle size distribution design scheme and its application in quartz ceramic preparation:

[0071] The difference between this comparative example and Example 3 is that the mass ratio of the first-level to fourth-level fused quartz particles in step 1 is different, and the other raw materials and steps are the same as those in Example 1; the specific mass ratio of the first-level to fourth-level fused quartz particles is: first-level particles: 35%, second-level particles: 35%, third-level particles: 20%, and fourth-level particles: 10%.

[0072] The properties of the quartz ceramic cores prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were tested. The testing methods are shown in Table 1, and the testing results are shown in Table 2.

[0073] Table 1

[0074]

[0075] Table 2

[0076] Core number Shrinkage / % Room temperature strength / MPa High temperature strength / MPa Open porosity / % <![CDATA[Bulk density / (g / cm 3 )]]> Example 1 1.78 10.902 28.55 31.23 1.68 Example 2 1.67 12.222 33.48 32.94 1.63 Example 3 1.98 14.065 37.87 31.31 1.66 Comparative Example 1 2.03 9.087 25.82 33.22 1.60 Comparative Example 2 1.95 9.110 26.20 32.13 1.62 Comparative Example 3 2.33 11.202 30.97 34.72 1.57 Comparative Example 4 2.06 11.401 31.82 33.50 1.59 Comparative Example 5 2.21 13.620 34.20 32.14 1.60 Comparative Example 6 1.99 13.025 34.98 32.50 1.62

[0077] It can be seen from Table 1 that by designing a four-level particle grading and applying it to quartz ceramic cores prepared in three different particle size ranges, it is successfully achieved that the quartz ceramic core can still maintain stable mechanical properties after being kept at 1550°C for 0.5h, and the high-temperature flexural strength of the core ranges from 28MPa to 38MPa.

[0078] The quartz ceramic core prepared according to the quartz particle grading design scheme of the present invention can significantly improve the high-temperature strength of the quartz ceramic core while controlling the shrinkage rate to less than 2%, thereby solving the problem of insufficient high-temperature strength of the quartz ceramic core that has long plagued the field of engine blade casting.

[0079] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for designing particle size distribution of low shrinkage ceramic green bodies, characterized in that: The following steps are involved: Sort the particle sizes by size, and regard different particle sizes as different diameters of equal-diameter spheres; select four particle sizes for grading, and determine the θ value at which two adjacent spherical particles are tangent to each other; query the spherical code table by the θ value to obtain how many spherical particles of small diameter can be wrapped around a spherical particle of large diameter; deduce the mass distribution ratio of spherical particles of two adjacent particle sizes according to the mass calculation formula and the sphere volume calculation formula, and obtain the optimal grading scheme; Among them, the particle sizes of the four particles are R1, R2, R3 and R4 from large to small, R2 = 0.633R1, R3 = 0.633R1 × 0.414, R4 = 0.633R1 × 0.225; The θ value of the tangent spherical particles of two particle sizes R1 and R2 is calculated by equations (1) and (2); sin01=R / (R1+R2)(1) 0=2aresin01(2) The calculation method of the θ value of the tangent spherical particles of two particle sizes R2 and R3, and the θ value of the tangent spherical particles of two particle sizes R3 and R4 is the same as above; Then, the mass distribution ratio of spherical particles of two adjacent particle sizes is calculated according to formula (3): In formula (3), m t is the mass of the t-level particles; m z is the mass of the z-level particle; k is the number of layers of the t-level particle encapsulating the z-level particle; R t is the radius of the t-level particle; R z is the radius of the z-level particle; Xt z is the number of z-level particles encapsulated by t-level particles; The source of the spherical code table is SLOANE NJ A. Nice arrangements of points on a sphere in various dimensions: Tables of Spherical Codes [R / OL]. (2012-1-15) [2024-03-20]. http: / / neilsloane.com / packings / dim3 / .

2. The method for designing particle size distribution of low shrinkage ceramic green bodies according to claim 1, characterized in that: k=1 or 2.

3. A process for preparing quartz ceramics, characterized in that: The following steps are involved: According to the low shrinkage ceramic body particle size gradation design method according to claim 1 or 2, the mass ratio of quartz particles of different particle sizes is calculated, the quartz particles are melted, a basic mineralizer is added, and then a molten plasticizer is added to obtain a mixed slurry, the mixed slurry is injected into a mold, sintered, and cooled to obtain a quartz ceramic.

4. The process for preparing quartz ceramics according to claim 3, characterized in that: The basic mineralizer is a combination of one or more of cerium oxide, zirconium oxide and titanium oxide.

5. The process for preparing quartz ceramics according to claim 4, characterized in that: The particle size range of the quartz particles is 100-1000 meshes; the particle size of the cerium oxide is 300-500 meshes; the particle size of the zirconium oxide is 300-500 meshes; and the particle size of the titanium oxide is 600-800 meshes.

6. The process for preparing quartz ceramics according to claim 4, characterized in that: The basic mineralizers are cerium oxide, zirconium oxide and titanium oxide.

7. The process for preparing quartz ceramics according to claim 6, characterized in that: In terms of mass percentage, quartz particles account for 70 to 100 parts, cerium oxide accounts for 1 to 5 parts, zirconium oxide accounts for 10 to 20 parts, titanium oxide accounts for 10 to 20 parts and plasticizer accounts for 15 to 20 parts.

8. The process for preparing quartz ceramics according to claim 3, characterized in that: The plasticizer consists of paraffin, beeswax and polyethylene in a mass ratio of 88-92:5-8:1-5.

9. The process for preparing quartz ceramics according to claim 3, characterized in that: When the mixed slurry is injected into the mold, the injection pressure is 3-6 MPa.

Citation Information

Patent Citations

  • Fused quartz ceramic hearth roll production process

    CN102826865A

  • High volume fraction RVE (Representative Volume Element) model generation method used for VCFEM (Voronoi Cell Finite Element Method) analysis

    CN106650018A

  • Preparation method of large solid quartz ceramic material

    CN109369163A

  • Method for preparing high-solid-phase content and low-viscosity ceramic slurry by using non-spherical ceramic particles

    CN110078481A

  • Phase change heat storage self-flowing refractory castable and preparation method therefor

    WO2021147411A1